(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Despite the fact that early neonatal morbidity is still prevalent even in term infants, there may be some practices that can be modified during the first hour after birth that can impact short-term outcomes. Materials and Methods: This is a prospective observational study which assessed the correlation between early breastfeeding (within 1 hour of birth) and neonatal morbidity in 320 term mother and newborn pairs admitted to a tertiary care teaching hospital. Results: Breastfeeding initiation within 1 hour of birth had a significantly lower composite morbidity rate in the first 7 days of life than delayed initiation (24.8% vs 45.3%, p<0.001). Early initiation was associated with lower frequencies of hypothermia (8.9% vs 21.7%, p=0.002), hypoglycemia (4.7% vs 12.3%, p=0.014), feeding difficulty (7.5% vs 18.9%, p=0.003), neonatal intensive care admission (6.5% vs 15.1%, p=0.012), and a shorter hospital stay (2.3±0.8 vs 3.0±1.4 days, p<0.001); after adjustment, delayed initiation independently increased the odds of neonatal morbidity (adjusted odds ratio 2.18, 95% confidence interval 1.31-3.63, p=0.003). Conclusions: Early breastfeeding initiation was thus linked to a clinically relevant decrease in early morbidity in term infants and is considered a time-sensitive aspect of standard delivery room practice.